2012
DOI: 10.1152/ajpendo.00591.2011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disruption of soluble epoxide hydrolase is protective against streptozotocin-induced diabetic nephropathy

Abstract: Cytochrome P-450 (CYP) epoxygenases metabolize arachidonic acid into epoxyeicosatrienoic acids (EETs), which play important roles in regulating cardiovascular functions. The anti-inflammatory, antiapoptotic, proangiogenic, and antihypertensive properties of EETs suggest a beneficial role for EETs in diabetic nephropathy. Endogenous EET levels are maintained by a balance between synthesis by CYP epoxygenases and hydrolysis by epoxide hydrolases into physiologically less active dihydroxyeicosatrienoic acids. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 53 publications
1
51
0
1
Order By: Relevance
“…Moreover, genetic disruption of sEH in STZ-induced diabetic mice show significant decreased levels of creatinine, BUN and urinary microalbumin excretion. Also, sEH-deficient diabetic mice showed reduced kidney injury [55]. These data indicate a role for EETs in the biology of proximal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, genetic disruption of sEH in STZ-induced diabetic mice show significant decreased levels of creatinine, BUN and urinary microalbumin excretion. Also, sEH-deficient diabetic mice showed reduced kidney injury [55]. These data indicate a role for EETs in the biology of proximal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 63%
“…We and others have recently demonstrated that decreased EETs availability in streptozotocininduced diabetic mice was associated with a marked degree of renal injury and apoptosis and this effect was significantly reduced by increased EETs availability via the inhibition of sEH [9,17]. Inhibition of sEH also reduces hyperglycaemia and pancreatic β-cell islet apoptosis and increases insulin secretion in steptozotocin-induced Type 1 diabetes [18].…”
Section: Discussionmentioning
confidence: 89%
“…COX-2 inhibition reduced renal injury in pre-clinical diabetic models including type 2 diabetic ZDF rat by decreasing glomerular and tubulointerstitial injury mediators in the kidney [18,19]. Apart from the COX-2 pathway, sEH pathway of arachidonic acid metabolism also contributes to the pathophysiology of diabetic kidney injury, and sEH inhibition ameliorated experimental diabetic nephropathy [40,48,49]. These earlier reports along with our data in the present study provide convincing evidence that in type 2 diabetic fatty ZDF rats the novel dual acting COX-2/sEH inhibitor PTUPB prevented the diabetic kidney injury by concurrently acting on COX-2 and sEH pathways.…”
Section: Discussionmentioning
confidence: 99%